The Process Occupying and Tending to the Use of Roads by Online Motorcycle Transportation - Tin Budi Utami (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
Jakarta is increasingly improving its public transportation services. At present, a breakthrough in the development of transportation has been made, especially related to the protocol road. These include expanding Transjakarta routes, Mass Rapid Transit, and Light Rail Transit. The addition of the number of modes of transportation has an impact on the addition of the number of stations or stops. However, it does not match by the availability of the government in procuring land for connecting transportation modes into deeper areas. The formal and informal transportation providers as an introduction to integrated transportation users still use the highway corridor as their place to raise, lower, and wait for passengers. Not yet found a place to raise, lower, and wait for those around the top of the officially integrated mode of transportation from the government or service providers. Therefore, this study was conducted to see how the division of land used by providers of the integrated transportation mode connector. This research method is to observe the spread of land use providers of formal and informal transportation services.